2017
DOI: 10.1016/j.bbmt.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Disruption Induced by Early Use of Broad-Spectrum Antibiotics Is an Independent Risk Factor of Outcome after Allogeneic Stem Cell Transplantation

Abstract: In allogeneic stem cell transplantation (ASCT), systemic broad-spectrum antibiotics are frequently used for treatment of infectious complications, but their effect on microbiota composition is still poorly understood. Here, in a retrospective analysis of 621 patients, who underwent ASCT at the University Medical Center of Regensburg and Memorial Sloan Kettering Cancer Center in New York, we assessed the impact of timing of peri-transplant antibiotic treatment on intestinal microbiota composition as well as tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
155
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(168 citation statements)
references
References 32 publications
7
155
4
2
Order By: Relevance
“…33 Regarding the timing of systemic antibiotic administration and the impact on GVHD, a retrospective study of 621 patients showed that early exposure to antibiotics (between days 27 and 0) resulted in significant reduction of Clostridiales with higher GVHD-related mortality. 34 These results suggest that, in the setting of allo-HCT, strategies to maintain beneficial anaerobes can contribute to better prognosis of patients. Beneficial effect on allo-HCT outcomes by fecal microbiota transplant also advocates the advantage of preserving anaerobes.…”
Section: Jones Et Al Showed In 1971mentioning
confidence: 91%
“…33 Regarding the timing of systemic antibiotic administration and the impact on GVHD, a retrospective study of 621 patients showed that early exposure to antibiotics (between days 27 and 0) resulted in significant reduction of Clostridiales with higher GVHD-related mortality. 34 These results suggest that, in the setting of allo-HCT, strategies to maintain beneficial anaerobes can contribute to better prognosis of patients. Beneficial effect on allo-HCT outcomes by fecal microbiota transplant also advocates the advantage of preserving anaerobes.…”
Section: Jones Et Al Showed In 1971mentioning
confidence: 91%
“…Another retrospective study indicated that the treatment of neutropenic fever with antibiotics such as imipenem-cilastatin and piperacillin-tazobactam was linked to increased GvHD-related mortality within 5 years [14]. Other recent studies also link prophylactic use of antibiotics to higher transplant-related mortality [15, 16]. …”
Section: Allogenic Hematopoietic Stem Cell Transplantation and Gvhdmentioning
confidence: 99%
“…The use of broad-spectrum antibiotics clindamycin, piperacillin-tazobactam, and imipenem-cilastatin are linked to GvHD in patients [15]. In allo-HSCT patients, common pathogens are Gram-negative bacteria (Enterobacteriaceae) and Gram-positive bacteria such as coagulase-negative Staphylococci , Streptococcus viridans , Enterococcus , and Candida species.…”
Section: Modulators Of the Gut Microbiotamentioning
confidence: 99%
“…Various factors are thought to contribute to dysbiosis after allo-HCT, including the use of conditioning agents with gastrointestinal toxicity, changes in food intake, use of specific prophylactic antibiotics, and administration of broad-spectrum antibiotics for infectious complications. Interestingly, different broad-spectrum antibiotics are associated with distinct changes in the microbiome and with variable rates of severe GVHD, in both mice and humans (68,86). In addition, the occurrence of GVHD itself appears to influence changes in the microbiome, perhaps due to effects on the intestinal epithelium and on ILCs regulating the epithelium-microbiome interface (59,62,65,70,71).…”
Section: Microbiome In Graft-versus-host Diseasementioning
confidence: 99%